BI-RADS 4 and 5 breast lesions: correlation between sonographic findings and histopathological results following ultrasound-guided FNAC - Abdullateef Aliasghar Mustafa (Kufa Journal for Nursing Sciences)
Background: clinical application of breast imaging reporting and data system (BI-RADS) lexicon for breast ultrasound useful to characterization of breast lesion and to inform the level of likelihood of malignancy.